Evaluation of colorectal cancer liver metastases based on liquid biopsy combined with folate receptor– Positive circulating tumor cells and HSP90 - Huang, Maosen; Cheng, Linyao; Mo, SiSi; Ru, Haiming; Mo, Xianwei; Yan, Linhai (Frontiers in Oncology, 2022)
Objective Liver metastasis of colorectal cancer (LMCRC) is a major cause of cancer-related deaths worldwide. We can reduce the mortality rate by discerning the risk of liver metastases in patients with colorectal cancer at an early stage. Hence, we combined the use of folate receptor (FR)–labeled circulating tumor cells (FR+CTCs) and the metastasis-related marker, heat shock protein 90 (HSP90), to screen patients with colorectal cancer and explore the prognostic factors of patients with high expression of FR+CTC and HSP90. Patients and methods A retrospective study of 356 patients with measurable colorectal cancer was performed. Negative enrichment and FR-targeted fluorescence quantitative PCR was utilized to detect FR+CTC. An ELISA kit was used to detect HSP90 expression. A timely follow-up study of patients with colorectal cancer was made. Results Colorectal patients with liver metastases showed high expression of FR+CTCs and HSP90. The diagnostic ability of the combined receiver operating characteristic curve of FR+CTC and HSP90 (area under the curve [AUC]=0.79, sensitivity 70.55%, specificity 92.66%) was significantly greater than that of a single index. The results of timely follow-up of patients showed that the high expression of FR+CTC significantly shortened the median disease-free survival (mDFS) of 36.5 months (95% confidence interval [CI]: 14.13–58.87, Logrank p < 0.0001) compared with the low expression cohort. The mDFS of the HSP90 high-expression cohort was significantly higher than that of the low-expression cohort (Logrank p = 0.0002), mDFS=58.47 months (95% CI: 37.12–79.81, Logrank p < 0.0001). We performed univariate and multivariate analyses to show that FR+CTC and HSP90 were risk factors for the progression of metastatic colorectal cancer (MCRC) disease. We then constructed a high- and low-risk score model of risk factors to evaluate MCRC. The diagnostic sensitivity of the risk model for MCRC was significantly improved (AUC=0.89, sensitivity 85.29%, specificity 81.33%), and the mDFS of patients in a high-risk group increased to 33.28 months (95% CI: 27.24–39.31, Logrank p < 0.0001). The establishment of the model improves the early screening of patients with MCRC. Conclusion Patients with colorectal cancer and high expression of FR+CTC and HSP90 are at risk of liver metastasis and this suggests a poor prognosis. Combining the two markers can improve the early screening and diagnosis of LMCRC patients. In addition, combining a multivariate risk model can further assist patients in appropriate stratification and the design of tailored treatment regimens. However, further validation these markers is needed before their routine clinical application.